Behaviour of stabilised peat: a field study - Islam, M.S.; Hashim, Roslan (2010)
The aim of this study is to observe engineering behaviour of stabilised peat soil by deep mixing method using various types of binder. A field model study has been conducted to stabilise peat using various types of binder. Various mechanical properties of stabilised peat, like undrained shear strength, unconfined compressive strength and shear strength was determined after 14 days of curing time. Scanning electron micrograph (SEM) and energy dispersive x-ray (EDX) test were also conducted to observe the microstructure of stabilised peat soil. From the test result, it was observed that the engineering properties of peat soil can be improved by stabilisation using additives.